Association of Craniovertebral Angle with Non- Specific Neck Pain and Functional Limitations among IT Professionals: Craniovertebral Angle with Non- Specific Neck Pain - Kalsoom, Humaira; Noor, Tayyaba; Andama, Gul; Javed, Ayesha; Waris, Abdul; Tamkeen, Maira; Khan, Qandeel Hamidullah; Iqbal, Irum (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
There was a strong link between workplace ergonomics and occupational diseases. Work-related illnesses contribute significantly to the total burden of occupational diseases. Information Technology (IT) professionals were more likely to experience physical activity limitations and nonspecific neck pain. Objective: To determine the association of craniovertebral angle (CVA) with nonspecific neck pain and functional limitations among IT professionals. Methods: Total 377 IT professionals participated in an observational cross-sectional survey. Non probability convenience sampling technique was used. CVA was evaluated using a manual goniometer, non-specific neck pain was measured using NPRS, and functional limitation was assessed by using the Neck Disability Index (NDI) questionnaire. The association of CVA with non-specific neck as well as functional restrictions was then found. Results: The mean age of this study was 29.43 ± 5.081. About 71.4% were males and 28.6% were females. The results showed that there was significant association of CVA with functional limitation (p value=0.01) and gender (p value =0.05). Also, a significant association was noted between functional limitations and non-specific neck pain (p value =<0.001). Contrastingly, no significant association of CVA observed with non-specific neck pain (p value =0.859) and with BMI (p value =0.721). Conclusions: The study concluded that there was no significant association of CVA with non- specific neck pain but recorded a significant association between CVA and functional limitation among IT professionals. Males were having a higher prevalence of forward head posture as compared to females.